Education of Girls: A Study of the National Programme for Education of Girls at the Elementary Level (NPEGEL) in Manipur, Mizoram and Tripura - Nuna, Anita (INDIAN EDUCATIONAL REVIEW, 2018)
The present research was to make an assessment of the contribution of the National Programme of Education for Girls at Elementary Level (NPEGEL), in enhancing enrolment and retention of girls in elementary education and to explore the benefits of the programme in overall development of girls. More specifically, the focus was on examining what kind of transformation has been brought in the educational scenario and overall development of girls in educationally backward blocks of the North Eastern States of India.